Mu’tazilah di Era Modern: Kajian Konsep Keadilan, Kebebasan, dan Rasionalitas dalam Pemikiran Islam - Riduan, Ahmad; Hartati, Zainap; Nasir, Muhammad (Jurnal Studi Islam dan Kemuhammadiyahan (JASIKA), 2025)
The lack of comprehensive studies discussing the relevance of Mu'tazilah thought in the context of contemporary Islamic social, political, and theological contexts is a major problem in Islamic studies today. In fact, the main values ​​of Mu'tazilah, namely justice, freedom, and rationality, have great potential to respond to various modern challenges, such as social injustice, restrictions on individual freedom, and the weak use of reason in religious and state life. This study aims to review the key concepts of Mu'tazilah and assess their relevance in answering contemporary issues of Muslims. The method used is literature study, through a critical review of classical and contemporary works that discuss Mu'tazilah thought. The results of the study show that Mu'tazilah thought remains relevant in the modern era. Their concept of justice supports the principles of social justice and the supremacy of law in a plural society. The view of freedom is in line with human rights values, although it must still consider local norms and ethics. The rationality they promote opens up space for constructive dialogue between religion and science. Thus, Mu'tazilah thought can be an important foundation in building a more just, rational, and civilized Islamic society, although it still requires reinterpretation to be in line with the dynamics of the times.